A novel variant in GLIS3 is associated with osteoarthritis. Issue 4 (7th February 2018) - Casalone, Elisabetta; Tachmazidou, Ioanna; Zengini, Eleni; Hatzikotoulas, Konstantinos; Hackinger, Sophie; Suveges, Daniel; Steinberg, Julia; Rayner, Nigel William; Wilkinson, Jeremy Mark; Panoutsopoulou, Kalliope; Zeggini, Eleftheria
Abstract : Objectives: Osteoarthritis (OA) is a complex disease, but its genetic aetiology remains poorly characterised. To identify novel susceptibility loci for OA, we carried out a genome-wide association study (GWAS) in individuals from the largest UK-based OA collections to date. Methods: We carried out a discovery GWAS in 5414 OA individuals with knee and/or hip total joint replacement (TJR) and 9939 population-based controls. We followed-up prioritised variants in OA subjects from the interim release of the UK Biobank resource (up to 12 658 cases and 50 898 controls) and our lead finding in operated OA subjects from the full release of UK Biobank (17 894 cases and 89 470 controls). We investigated its functional implications in methylation, gene expression and proteomics data in primary chondrocytes from 12 pairs of intact and degraded cartilage samples from patients undergoing TJR. Results: We detect a genome-wide significant association at rs10116772 with TJR (P=3.7×10 −8 ; for allele A: OR (95% CI) 0.97 (0.96 to 0.98)), an intronic variant in GLIS3, which is expressed in cartilage. Variants in strong correlation with rs10116772 have been associated with elevated plasma glucose levels and diabetes. Conclusions: We identify a novel susceptibility locus for OA that has been previously implicated in diabetes and glycaemic traits.